The Impact of HIV on Oral Health and Subsequent Use of Dental Services - Aram Dobalian, PhD, JD; Ronald M. Andersen, PhD; Judith A. Stein, PhD; Ron D. Hays, PhD; (Blackwell Synergy, 2003)
This study examined differences in health and access to dental services among a nationally representative sample of patients with HIV using Andersen’s Behavioral Model of Health Services Use